Empowering legal literacy: the impact of social media influencers in Malaysia / Mohd Syahril Ibrahim - Ibrahim, Mohd Syahril (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Social media influencers are individuals who use significant power in shaping consumer decisions and opinions through their online presence and interactions with followers (Worthington, 2023). They play a crucial role in various spheres, from marketing products and services to disseminating political information and influencing societal attitudes. As of 2023, Malaysia had around 30 million active social media users, which represents a significant portion of the population. This widespread usage indicates a vast potential audience for influencers, including those focusing on legal issues. In the legal spectrum, social media influencers can shape legal awareness through their content in social platforms (Zainuddin & Salle, 2022; Cai & Zhang, 2023).